Relational wellbeing: A theoretical and operational approach - Sarah C. White (University of Bath, Centre for Development Studies (CDS), 2015)
Relational wellbeing is an emergent construct grounded in the interpretivist tradition in social science. It approaches people as subjects, and aims to understand the ways they see the world in as near to their own terms as possible. This contrasts with mainstream approaches to subjective dimensions of wellbeing in psychology and economics, which take a positivist approach, positioning people as objects, whose variability is to be investigated through observation rather than inter-locution.Since the recent upsurge in interest in wellbeing has focused on its subjective dimensions, or 'happiness', it seems paradoxical that the social science traditions that emphasise subjectivity should thus far have been marginalised in wellbeing debates. This paper draws together recent contributions which take a more relational, qualitative approach, as a step towards reversing this trend. The final section considers how relational wellbeing may be operationalised in policy and practice.
Keywords: 330; relational wellbeing; subjective wellbeing; subjectivity; qualitative methods; policy and practice